An outbreak of COVID-19 after a pilgrimage to Medjugorje due to Delta sub-lineages - Lo Presti, Alessandra; Rubino, Salvatore; Ibba, Gabriele; Ambrosio, Luigina; Di Martino, Angela; Ferraro, Federica; Rapiti, Alessia; Maraglino, Francesco; Frisicale, Emanuela Maria; Rezza, Giovanni; Angioj, Flavia; Uzzau, Sergio; et al. (The Journal of Infection in Developing Countries, 2024)
Introduction: A COVID-19 outbreak occurred at the end of October 2021 among pilgrims returning from Medjugorje (Bosnia and Herzegovina). Methodology: Whole genome sequencing (WGS) of SARS-CoV-2, epidemiological data, and phylogenetic analysis were used to reconstruct outbreak dynamics. Results: The results suggest that only in one case, associated with the SARS-CoV-2 sub-lineage AY.9.2, it is possible to trace back the place of contagion to Medjugorje, while the other cases were likely to be acquired in the country of origin. Conclusions: The combined use of phylogenetic data derived from WGS, and epidemiological data allowed us to study epidemic dynamics and to formulate a possible hypothesis on the place of exposure to SARS-CoV-2. The identification of different sub-lineages of the SARS-CoV-2 Delta variant also suggested that different chains of transmission contributed to the outbreak.